(e, 2e) on helium: Complete agreement between experiment and theory - Ren, X.; Bray, Igor; Fursa, Dmitry; Pflüger, T.; Senftleben, A.; Dorn, A.; Ullrich, J. (2012)
Single ionization of helium by 70.6 eV electron impact is studied in a comprehensive experiment covering a major part of the entire collision kinematics and the full 4p solid angle for the emitted electron. The absolutely normalized triple differential experimental cross sections are in excellent agreement with convergent close-coupling (CCC) calculations. We conclude that the problem of electron impact single ionization of helium has been solved accurately in the present energy regime.